Double-key unlocking device - LIU XIAOJUN; WEI YIXING; ZHANG ZHOUHAI; FANG SICONG (2025)
The utility model provides a double-key unlocking device. The double-key unlocking device comprises a shell; the first key assembly is movably arranged in the shell and has a state of being stored in the shell and a state of extending out of the shell; the second key assembly is movably arranged in the shell and has a state of being stored in the shell and a state of extending out of the shell; the interlocking piece is movably arranged between the first key assembly and the second key assembly, when one of the first key assembly and the second key assembly is switched to extend out of the shell, the interlocking piece is driven to move, and the interlocking piece extends into and locks the other one of the first key assembly and the second key assembly. The key solves the problem that a key in the prior art is inconvenient to carry and use. 本实用新型提供了一种双钥匙解锁装置，包括：壳体；第一钥匙组件，第一钥匙组件活动设置在壳体内，且具有收纳至壳体内的状态和伸出壳体的状态；第二钥匙组件，第二钥匙组件活动设置在壳体内，且具有收纳至壳体内的状态和伸出壳体的状态；互锁件，互锁件活动设置在第一钥匙组件和第二钥匙组件之间，第一钥匙组件和第二钥匙组件中的一者切换伸出壳体的状态时带动互锁件